Automatic algorithm applied for calculating thermal conductivity by transient plane source method - Jia, Zhijie; Yang, Liping; Cao, Chengcheng; Li, Huidong; Luo, Caiyun; Tao, Te; Zhong, Qiu; Xu, Zijun; Chen, Zezhong (Penerbit Universiti Kebangsaan Malaysia, 2024)
As a thermal conductivity measurement method, Transient Plane Source (TPS) method has gained much popularity because of its broad applicability, short measurement times, high precision and simple sample preparation. However, the accuracy of thermal conductivity calculations based on temperature rise data is often hindered by factors such as probe thickness, contact thermal resistance, and input power. Currently, there is no standardized criteria for selecting effective temperature rise data for thermal conductivity calculation. Consequently, the accuracy of results are limited by the operator’s understanding of the TPS methods, and repeatability of the results is often poor. To address this issue, an automatic algorithm based on the international standard (ISO22007-2:2008) is proposed in this paper. By applying this algorithm to the measurement of different materials, it has been demonstrated that the proposed algorithm can produce more precise and consistent results than the conventional method. Additionally, the integration of the time window function max/tθ, typically utilized solely for result validation in conventional methods, further enhances the objectivity and reproducibility of the results obtained by the automatic algorithm